(untitled) (Research, Society and Development, 2022)
To analyze the prevalence and socioeconomic determinants of NCDs in adults in the state of Pernambuco, in 2015/2016. This is a cross-sectional study, with a sample of 1019 adults, based on the IV State Health and Nutrition Survey. Possible associations of CNCDs with factors were analyzed by means of logistic regression, considering as statistically significant those with p value < 0.05. The prevalence of CNCD was 62.5%, being higher among men (68.1%), with a progressive increase from the age group of 30-39 years, among those with a lower level of education (80.2 %), of white race (69.1%) and who did not receive a family allowance (70.1%). In the multivariate model, the variables associated with CNCD were: sex, age, education, race and family allowance. There was a high prevalence of at least one CNCD and a significant association with socioeconomic variables: low education, white race and not receiving a family allowance. These results suggest the need to intensify actions aimed at socioeconomic determinants, especially in the most vulnerable populations, with a view to better controlling NCDs.